2023
DOI: 10.1371/journal.pone.0279857
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s data governance preferences for their mental health data: MindKind Study findings from India, South Africa, and the United Kingdom

Abstract: Mobile devices offer a scalable opportunity to collect longitudinal data that facilitate advances in mental health treatment to address the burden of mental health conditions in young people. Sharing these data with the research community is critical to gaining maximal value from rich data of this nature. However, the highly personal nature of the data necessitates understanding the conditions under which young people are willing to share them. To answer this question, we developed the MindKind Study, a multin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…While complete democracy was often seen as infeasible, a review panel of either volunteers or paid community members was viewed as a good compromise, which echoes the findings of other research [ 12 ]. However, this finding conflicts with results from the quantitative arm of the MindKind Study, which found that UK participants preferred democracy or a professional review panel over a voluntary panel [ 21 ]. This may be because of the extensive educational materials provided to those in the qualitative arm of the study or because of more subtle differences in the phrasing of options.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…While complete democracy was often seen as infeasible, a review panel of either volunteers or paid community members was viewed as a good compromise, which echoes the findings of other research [ 12 ]. However, this finding conflicts with results from the quantitative arm of the MindKind Study, which found that UK participants preferred democracy or a professional review panel over a voluntary panel [ 21 ]. This may be because of the extensive educational materials provided to those in the qualitative arm of the study or because of more subtle differences in the phrasing of options.…”
Section: Discussionmentioning
confidence: 65%
“…Participants were enthusiastic about data being as accessible as possible to a variety of people because data access was seen as a public good. Our broader, global study found some differences by region, so we report findings specific to the United Kingdom [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MindKind Study was a mixed methods international collaboration to investigate the feasibility of a global databank to derive mental health insights [10]. The MindKind Study included a quantitative arm that recruited participants to collect their mental health data via a mobile application and a qualitative public deliberation arm, which was conducted in concert with sites in India, South Africa, and the United Kingdom (UK).…”
Section: Introductionmentioning
confidence: 99%
“…We note that the findings discussed in this manuscript do not include any data from the main MindKind study or any of the randomized arms. The objective of this manuscript was to describe the impact of coproduction with youth on different stakeholder groups [ 32 ]. Coproduction with youth was designed to influence both the qualitative and quantitative study arms (ie, youth were coresearchers), and we evaluated such impact of youth acting as coresearchers on key stakeholder groups.…”
Section: Introductionmentioning
confidence: 99%